“Remain in the Calling in Which You Were Called” (1 Cor 7:20): A Post Supersessionist Reading of 1 Corinthians - Kar Yong Lim (Religions, 2023)
This essay explores how Paul negotiates and constructs social identity for the Christos-followers in Corinth from a post-supersessionist perspective by using the Social Identity Theory. Focusing on a close reading of two controversial passages taken from 1 Corinthians (1 Cor 7:17–24 and 9:19–23), this essay argues that there is continuation of existing social identities of both the Jewish and gentile Christos-followers. In the Christos-movement, Jews were not expected to give up their place of belonging in order to become Christos-followers. Likewise, gentiles were not expected to leave behind their previous identity and embrace Jewish practices in order to become the people of God who worship the God of Israel. While the existing social identities continue, Paul also creatively transforms them. Reflection on the implication of this reading for contemporary ethnic Chinese Christos-followers in Muslim-majority Malaysia is also offered.